Exploring the relationship between psoriasis and vitamin D - Aleksandra Kiełczewska; Grzegorz Szcześniak; Anna Kiełczewska (Journal of Education, Health and Sport)
Introduction and purpose: Psoriasis is a chronic, inflammatory skin condition that affects millions of individuals worldwide. Recent research has suggested a potential link between psoriasis and vitamin D deficiency. This review paper aims to examine the existing literature on the relationship between psoriasis and vitamin D, exploring the potential role of vitamin D in the pathogenesis and management of this debilitating skin disorder.